Malaysia-Thailand, Beyond the New Ornamentalism in Contemporary Jewelry - Veerawat Sirivesmas; Alias Yussof (IJCAS (International Journal of Creative and Arts Studies), 2015)
Towards a new perspective of pedagogical approach and constructive criticism in art practice based education, the investigation is focusing on Malaysia-Thailand contemporary art & craft jewelry in academic area. From the traditions of national craft heritage the jewelry, silverware and metalwork is now a day almost lost its conservation to their modern people and its community. The Jewelry is representative of national artifact of high crafting. It passes through present where number of contemporary art objects and lifestyle design gadgets are already dominating new behavioral to society. From this perspective, the different between lifestyle and culture can shape up concept and identity of contemporary jewelry. Where the traditional elements can still remain in somewhere with us! Many academicians, designer makers are working and try to modernize these national prides which obtained the traditional implicit knowledge and local wisdoms. The art and design education also concerns this matter by raising many cultural topics involved into curriculum. It becomes a subject that students can reflect their role of preservation or expression on their cultural contents. The cross cultural perspective of rising perception of the author on contemporary jewelry education between Thailand and Malaysia has begun in 2008 by the invitation of Department of Fine Metal, Universiti Teknologi MARA (UiTM) Malaysia. The UiTM invited a staff (author ) of Department of Jewelry Design, Silpakorn University Thailand, as an external assessor for final year student assessment. The participatory research occasionally began from that point under the pedagogical framework. Observations, interviews, critics on student artworks, were the main activity process that both of students and staff of institution also interacted according to the process of assessment. Definitely, the differentiation between the students’ outcome of jewelry project in Malaysia and Thailand are obviously divergence. However, the traditional ornament of each country and cultural influences also be noticed that have been frequently inspired in students’ work. The constructive criticism was always the core discussion during the students’ assessment and exit meeting with UiTM department members. During year by year, there were number of improvements can be noticed not only on the students’ outcomes but also the academic relationship through collaboration activities that create among two institutions.